Preparation of Activated Carbons from Sawdust by Chemical Activation - Huiping Zhang; Ying Yan; Lichun Yang (Adsorption Science & Technology)
Activated carbons were prepared from sawdust by chemical activation with H 3 PO 4 . The effects of various parameters such as the impregnation ratio, activation temperature and time on the nitrogen adsorption isotherms, specific surface areas and pore volumes of the activated carbons were measured and analyzed in order to optimize the operational conditions. The nitrogen adsorption capacity of the activated carbons was significantly affected by the impregnation ratio and the activation temperature. The most important operational parameter in chemical activation with H 3 PO 4 was found to be the H 3 PO 4 /sawdust impregnation ratio. The specific surface area of the activated carbon prepared with a 1:1 H 3 PO 4 /sawdust ratio and activated at 500°C for 90 min attained the relatively high value of 1642 m 2 /g. The experimental results show that, under the experimental conditions studied, an activated carbon containing well-developed micropores and mesopores exhibiting improved nitrogen adsorption properties can be obtained via a H 3 PO 4 activation process under the optimum operation conditions, viz. activated with an impregnation ratio of 1.0–1.5H 3 PO 4 /sawdust at 500°C for 60–90 min.